EVALUATION OF ANTI-BACTERIAL AND ANTI-BIOFILM PROPERTY OF NARINGIN LOADED NANO-HYDROXYAPATITE AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI (Journal of Pharmaceutical Negative Results, 2023)
Bacterial infections are one of the most often occurring complications with medical implants and reconstructive bone surgery, and they still remain to be one of the leading causes of failure following bone repair. One of the major challenges is treating the infection caused by microorganisms. To overcome this, systemic antibiotics are crucial for successful bone regeneration surgery. Regardless of extensive, high-dose therapies these drugs cannot reach the target surgical area and also antibiotic resistance develops. Hence, the purpose of this research was to develop a biomaterial with antibacterial potential for bone tissue engineering. The hydroxyapatite nanoparticles (n-HA) is widely employed in bone therapy owing to its good biocompatibility, bioactivity, osteoconductivity and has a topography that resembles the architecture of natural bone. Here, we present the experimental findings of the antibacterial activities of pure n-HA and n-HA+NA biocomposite compounds as assessed by Gram- positive and Gram-negative bacterial strains. According to the findings, HA nanoparticles that have been functionalized with naringin exhibit excellent antibacterial activity and may find use in the medical and dental fields as a bone-regenerating material.